Autologous Fat Grafting Reduces Pain in Irradiated Breast: A Review of Our Experience - Fabio Caviggioli; Luca Maione; Francesco Klinger; Andrea Lisa; Marco Klinger (Stem Cells International)
Introduction. Pain syndromes affect women after conservative and radical breast oncological procedures. Radiation therapy influences their development. We report autologous fat grafting therapeutical role in treating chronic pain in irradiated patients. Materials and Methods. From February 2006 to November 2014, we collect a total of 209 patients who meet the definition of “Postmastectomy Pain Syndrome” (PMPS) and had undergone mastectomy with axillary dissection (113 patients) or quadrantectomy (96 patients). Both procedures were followed by radiotherapy. We performed fat grafting following Coleman’s procedure. Mean amount of adipose tissue injected was 52 cc (±8.9 cc) per breast. Seventy-eight in 209 patients were not treated surgically and were considered as control group. Data were gathered through preoperative and postoperative VAS questionnaires; analgesic drug intake was recorded. Results. The follow-up was at 12 months (range 11.7–13.5 months). In 120 treated patients we detected pain decrease (mean ± SD point reduction, 3.19 ± 2.86). Forty-eight in 59 patients stopped their analgesic drug therapy. Controls reported a mean ± SD decrease of pain of 1.14 ± 2.72. Results showed that pain decreased significantly in patients treated (p<0.005, Wilcoxon rank-sum test). Conclusion. Our 8-year experience confirms fat grafting effectiveness in decreasing neuropathic pain.